The impacts of oxytetracycline on humification during manure composting can be alleviated by adjusting initial moisture contents as illustrated by NMR - Yao FENG; Gui-zhen WANG; Yuan-wang LIU; Deng-miao CHENG; Shuang-hu FAN; Quan-sheng ZHAO; Jianming XUE; Shu-qing ZHANG; Zhao-jun LI (Journal of Integrative Agriculture, 2021)
Oxytetracycline (OTC) residues have been found in soil and water, and they may pose potential risks to agricultural ecological environments. One of the most impactful ways for OTC to enter the soil and water environments is through excrement used as organic fertilizer. Therefore, it is important to remove OTC during manure composting and to understand the transformation of the organic materials during composting in the presence of OTC. In the present paper, chicken manure and wheat sawdust spiked with OTC were composted under different initial moisture contents (MC) to evaluate the degradation of OTC and changes of organic matter during the composting process. The MC has a significant effect on OTC degradation during composting. A higher MC of 65% was more conducive to OTC degradation (77.4%) and compost maturity compared to the lower MC. However, the higher MC of 65% could increase the ammonia volatilization by promoting nitrification compared to the lower MC. An increase in the initial MC could improve the composting temperature. NMR results illustrated that the presence of OTC could affect the internal transformation of aliphatics, and OTC inhibited compost humification. Thus, an initial MC of 55–65% can alleviate the impacts of OTC on humification during manure composting.